Canadian International Petroleum Conference 2000
DOI: 10.2118/2000-078
|View full text |Cite
|
Sign up to set email alerts
|

Use of Coupled Reservoir and Geomechanical Modelling for Integrated Reservoir Analysis and Management

Abstract: Reservoir engineering (and simulation) have historically paid little attention to the geomechanical behaviour of porous media. However, a number of important (primarily unconventional) recovery processes can be properly engineered only by including this effect (e.g., thermal recovery in oil sands, compaction drive in soft and unconsolidated reservoirs, chalk reservoirs, stress sensitive and microfractured media, waterflooding at fracture pressure, waste injection, coal seam stimulation, etc.). In addition, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Oil sands in the McMurray Formation have in-situ interlocked fabric configurations, previous experimental studies by Dusseault and Morgenstern (1978), Agar et al (1986), Kosar et al (1987), Oldakowski (1994), Scott et al (1994), Chalaturnyk (1996), Samieh and Wong (1996) and Touhidi-Baghini (1998) and numerical studies by Chalaturnyk (1996), Settari et al (2001), Li (2006), Du and Wong (2007) and Azad and Chalaturnyk (2011) have shown that geomechanics can play a significant role in the SAGD process. Thus, conventional simulation techniques may provide less than optimum results for the response of the reservoir and coupled geomechanical flow simulation should be considered.…”
Section: Introductionmentioning
confidence: 91%
“…Oil sands in the McMurray Formation have in-situ interlocked fabric configurations, previous experimental studies by Dusseault and Morgenstern (1978), Agar et al (1986), Kosar et al (1987), Oldakowski (1994), Scott et al (1994), Chalaturnyk (1996), Samieh and Wong (1996) and Touhidi-Baghini (1998) and numerical studies by Chalaturnyk (1996), Settari et al (2001), Li (2006), Du and Wong (2007) and Azad and Chalaturnyk (2011) have shown that geomechanics can play a significant role in the SAGD process. Thus, conventional simulation techniques may provide less than optimum results for the response of the reservoir and coupled geomechanical flow simulation should be considered.…”
Section: Introductionmentioning
confidence: 91%
“…The model, which couples a multiphase reservoir simulator with a 3-D finite element solution of deformations and stresses, has been used extensively for geomechanical studies of compaction, thermal operations and similar problems 8,9 . For the modeling of microseismicity, it is important to couple the fracture propagation both in terms of fluid flow and deformations (fracture opening), as shown in Fig.…”
Section: The Coupled Fracture Modelmentioning
confidence: 99%
“…These effects usually become more pronounced at elevated pressures and are highly dependent on the in-situ conditions of the reservoir such as stress distribution, mechanical properties and fluid (water) mobility. Extensive research has been undertaken in the area of oilsands geomechanics for thermal recovery applications over the last few decades, including a field-scale experimental program at the AOSTRA's Underground Test Facility (Chalaturnyk, 1996) as well as comprehensive laboratory programs (Daussalt and Mogenstern, 1978;Kosar et al, 1987;Agar et al 1987;Oldakowski, 1994;Scott et al, 1994;Samieh and Wong, 1997;and Tohidi-Baghini, 1998), elaborate analytical modeling (Azad and Chalaturnyk 2010;Hosseini 2015) and numerical simulation studies (Tortike, 1991;Chalaturnyk, 1996;Settari and Mourits, 1998;Settari et al, 2001;Du and Wong, 2009;Li and Chalaturnyk, 2009;Azad and Chalaturnyk, 2011;Shen et al 2014).…”
Section: Introductionmentioning
confidence: 99%